Emerson's PLM journey in a culture of autonomous divisions - Maenza, Tano (Knovel, 2009)
To inject efficiencies in its engineering processes and to foster new ways of inter-division collaboration, this decentralized, global manufacturer is standardizing PLM technologies and product development practices. Its secret weapon: A PLM Center of Excellence.
Keywords: Product life cycle.; Production management.; Industrial engineering.; elektronické knihy; electronic books